Al Jami' al Sahih wa huwa Sunan al Tirmidhi - Abi Isa Muhammad Ibn Isa Ibn-Surah (Dar al Fikr)
ws.jl.1,5.c.1-3,jl.2-3,c.1-2,jl.4.c.1/stoc5, jil.1=c1-2, jil.2=c1-2, jil.3=c.1, jil.4=c.1, jil.5=c.1-2,jil.2.c3